Reentry high altitude pulmonary edema in the Himalayas - Baniya, S; Holden, C; Basnyat, B (Mary Ann Liebert, 2018)
Reentry high altitude pulmonary edema in the Himalayas. High Alt Med Biol. 16:000-000, 2017.-Reentry high altitude pulmonary edema (HAPE), a subset of HAPE, is a well recognized, life-threatening illness documented almost exclusively in the North and South Americans, who live at high altitude (>2500 m) and return to their homes after a brief sojourn of days to months at lower altitude. This phenomenon has not been reported in Sherpas or other people of Tibetan origin in Nepal or India. And it has rarely been reported from Tibet. In this study we document a case of reentry HAPE in Manang region (3500 m) of Nepal in a 7-year-old Nepali boy of Tibetan ancestry who fell ill when he ascended to his village (Manang, 3500 m) from Besisahar (760 m) in 1 day in a motor vehicle after spending the winter (December to March) at Besisahar with his family. With more motorable road access to high altitude settlements in the Himalayas, reentry HAPE may need to be strongly considered by healthcare professionals in local residents of high altitude; otherwise life-threatening complications may ensue as in our case report.